New Results for Multivalued Mappings in Hausdorff Neutrosophic Metric Spaces - Mathuraiveeran Jeyaraman; Hassen Aydi; Manuel De La Sen (Axioms, 2022)
The fundamental goal of this paper is to derive common fixed-point results for a sequence of multivalued mappings contained in a closed ball over a complete neutrosophic metric space. A basic and distinctive procedure has been used to prove the proposed results.